Faktor Penyebab Ketidaklengkapan Rekam Medis Rawat Inap di RSUD dr. Saiful Anwar Malang - Ana Nafidatul Khoiroh; Novita Nuraini; Maya Weka Santi (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
One of efforts to improve the quality of healthcare facilities is to improve the quality of medical record services including completeness, speed and accuracy in providing information for health care needs. A complete and accurate medical record can be used as a reference to health services, legal bases, supporting information to improve medical quality, medical research and be used as a basis to assess the performance of hospitals. The purpose of this research identifies the factors causing the incompleteness of the replenishment of inpatient medical record in the RSUD Dr. Saiful Anwar Malang. The type of research used is qualitative. Data collection techniques by way of document study, interviews and observation. Document studies are conducted on 100 inpatient medical record documents that have not been conducted assembling, while the interview is conducted to the IRNA 2 medical record officer to determine the factors causing the incompleteness of medical record documents. Observation is done to complete the interview data. The results of the analysis on 100 inpatient medical record files were obtained that the incomplete number of medical records was 79%, with the most incompleteness presentation on the responsibilities of the doctor which includes medical resumes, casemix sheets, and surgery reports. The interview and observation results show that the main causation factor for the filing of an inpatient medical record of a surgical ward is from the doctor's awareness and discipline in filling in the medical record documents. As a solution to improve the completeness of medical record filling is by spur motivation and increase the discipline of doctors in filling medical record documents by providing reward and punishment and to repair SOP filling medical record of hospitalizatio.